Оцінно-пізнавальний аспект щоденникової мовної картини світу - Сирко, І. (Культура слова, 2021)
Стаття присвячена дослідженню параметрів лінгвалізації картини світу в текстах літературної діаристики. Акцентовано на аксіолого-гносеологічному та онтологічному аспектах вивчення мовної картини світу. Зазначено, що аксіолого-гносеологічний аспект передбачає розгляд кількох визначальних параметрів, пов’язаних із процесом створення текстів традиційних щоденників: егоцентрованість, автокомунікативність та синхронізованість вербалізації подій із моментом їх звершення. Доведено, що в текстах літературної діаристики вказані параметри зазнають трансформацій, пов’язаних із професійним статусом авторів: егоцентрованість набуває більшої варіативності, автокомунікативність трансформується у двоадресність, а синхронність фіксації подій з моментом їх звершення втрачає стабільність. Today, within diary studies, it is advisable to emphasize the study of the diary as a literary genre, historical or biographical source; to characterize diary texts with the use of culturological, philosophical, psychological and other approaches. Linguistic studies of diary texts are mostly focused on the description of basic typological characteristics. However, the verbalization of the national and individual, as well as chronologically and spatially marked linguistic picture of the world - is only an episodic fragment of modern linguistic diary studies. The parameters of lingualization of the picture of the world in the texts of literary diaristics have not been thoroughly studied yet. It is known that the linguistic picture of the world is a set of knowledge about the world reflected in the language, as well as ways to obtain and interpret new knowledge. Among the key aspects of its study are evaluative-cognitive (or axiological-epistemological) and ontological, which involve identifying the specifics of verbalization in the diary texts of ways of cognition and interpretation of the world, as well as individual knowledge systems of the authors. Consideration of the axiological-epistemological aspect of the linguistic picture of the world provides several parameters related to the process of creating the texts of traditional diaries. In particular, they are: egocentricity, autocommunicativeness, as well as synchronicity of recording the events with the moment of their completion. In the texts of literary diaristics, these parameters undergo qualitative transformations that are related to the professional status of the authors. Such transformations cause egocentricity to become noticeably variable, autocommunicativeness is transformed into biaddressability, and the synchronicity of the process of fixing events with the moment of their completion loses its stability.